PENGARUH SISTEM INFORMASI DAN MOTIVASI TERHADAP KINERJA: TINJAUAN LITERATUR - Ibrahim Bali Pamungkas; Imbron Imbron; Hafis Laksmana Nuraldy (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The purpose of this research is a). Identify the influence of information systems on performance based on empirical studies of the last 6 years, b). Identify the influence of motivation on performance based on empirical studies of the last 6 years. The method for searching for article data sources is through the GARUDA database (2017-2022) to retrieve relevant articles published in Indonesian. Key terms and phrases related to information systems and motivation on performance using abstract Literature Review or research journal texts are reviewed before being included in the review according to the criteria. Based on 22 journals for the last 6 years that were reviewed, the results stated that the results of a review of 22 research journals contained 5 journals which stated that the information system had no effect and 17 journals stated that there was an influence, then the results of a review of 22 research journals found 2 journals which stated that motivation was not influential and 20 journals stated that there was influence.